Strategi Dinas Koperasi & UMKM Dalam Pemberdayaan Home Industry Tahu Kota Kediri (Studi Pada Dinas Koperasi & UMKM dan Home Industry Tahu Kelurahan Tinalan) - Raden Roro Ratna Sari Setyo Jaya Wardani (Jurnal Administrasi Publik, 2016)
Abstract: The Strategies of Department of Cooperatives and UMKM (Micro, Small, and Medium Enterprises)in Tofu Home Industry Empowerment, Kediri Regency (Study of Department of Cooperatives and UMKM (Micro, Small, and Medium Enterprises)and Tofu Home Industry in Tinalan Village). Kediri Regency is one of a city in a strategic position, however,  Tofu Home Industry located in Tinalan Village has not been well-developed. Several limitations above must be improved in order to acceleratethe development of Tofu Home Industry, regarding the fact that Tofu is the special traditional food which needs to be conserved. Through Department of Cooperatives and UMKM (Micro, Small, and Medium Enterprises), the government of Kediri Regency empower the Tofu Home Industry to be able to develop widely in the future. This study used descriptive method with qualitative approach and has 2 focuses which are: (1) The Strategies of Department of Cooperatives and UMKM (Micro, Small, and Medium Enterprises) included Human Resource Training, Marketing, and Capital and Empowerment of Tofu Home Industry in Kediri Regency including the approach used by Department of Cooperatives and UMKM in the empowerment of Tofu Home Industry and the processes in empowering Tofu Home Industry; (2) Supporting Factors and Obstructing Factors. The data sources were obtained from informants, events, documents, and primary and secondary data. The data were collected through interview, observation, and documentation. The analysis were conducted using Seidel (2013) through observation step, data grouping, and interpreting the data or discovering the phenomena being examined.   Keywords:empowerment, home industry, tofu.   Abstrak: Strategi Dinas Koperasi dan UMKM Dalam Pemberdayaan Home Industry Tahu Kota Kediri (Studi Pada Dinas Koperasi dan UMKM dan Home Industry Tahu Kelurahan Tinalan).Kota Kediri adalah salah satu kota yang terletak pada posisi yang strategis. Home Industry Tahu yang ada di Kelurahan Tinalan masih belum bisa mengembangkan usahanya dengan baik. Yang disebabkan oleh pemasaran yang belum baik, keterbatasan modal usaha, kualitas sumber daya manusia yang masih belum terampil. Pemerintah Kota Kediri melalui Dinas Koperasi dan UMKM Kota Kediri melakukan pemberdayaan kepada home industry Tahu yang akan mampu berdaya dan berkembang lebih baik untuk home industry Tahu ke depannya. Penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif dan ada 2 fokus penelitian, yaitu: (1) Strategi  Dinas Koperasi dan UMKM yang meliputi Pelatihan Sumber Daya Manusia, Pemasaran, dan Permodalan dan Pemberdayaan Home Industry Tahu Kota Kediri yang meliputi: Pendekatan yang digunakan Dinas Koperasi dan UMKM dalam Pemberdayaan Home Industry Tahu dan Proses-proses dalam Pemberdayaan Home Industry Tahu; (2) Faktor Pendukung dan Faktor Penghambat. Sumber data berasal informan, peristiwa, dokumen serta dari jenis data primer dan data sekunder. Data dikumpulkan melalui teknik wawancara, observasi, dan dokumentasi. Analisis data menggunakan Seidel (2013) melalui tahap pengamatan atau observasi, penglompokan data yang sudah didapat, dan menemukan fenomena yang sedang diteliti. Kata kunci:pemberdayaan, home industry, Tahu